INFLUENCE OF SOME TECHNOLOGICAL FACTORS ON THE QUALITY PRODUCTION OF RAPE CULTURE UNDER THE NORTH WESTERN CONDITIONS OF ROMANIA - Emil Luca; Felicia Boar; M. Chintoanu; Cecilia Roman; Laura Cristina Luca (Agricultura, 2014)
The paper presents the results of studies regarding the influence of irrigation on the rape quality yieldÂ  culture in an important area of Transylvania, respectively Satu Mare, during 2009-2011. In experiments tested a new biological material, varieties and hybrids with high yield. The experimental factors studied at Satu Mare were - factor A - water regime, factor B - variety, (especially biological material) and factor C - plant density.